2016
DOI: 10.1002/ajh.24361
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of rapid (1,000 mg in 1 hr) intravenous iron dextran for treatment of maternal iron deficient anemia of pregnancy

Abstract: Maternal iron deficiency anemia (IDA) is associated with risk of adverse perinatal outcomes. Oral iron is recommended to reverse anemia, but has gastrointestinal toxicity and frequent non-adherence. Intravenous (IV) iron is reserved for intolerance of, or unresponsiveness to, oral therapy, malabsorption, and severe anemia (1% with hemoglobin [Hgb] levels <7 g/dL). With rare (<100 per one million) adverse events (AEs) ability to infuse a sufficient dose of low molecular weight iron dextran (LMWID) over 60 min, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 33 publications
2
29
0
Order By: Relevance
“…65 An observational study of 189 women treated with LMW iron dextran in second and third trimester reported no severe adverse events and only 2% transient infusion reactions. 66 These results corroborated outcomes in other studies showing safety of LMW iron dextran, 67,68 which allows complete replacement of IV iron in a single infusion over 15 to 60 minutes. Despite well-established safety, LMW iron dextran still requires a test dose.…”
Section: Hepcidinsupporting
confidence: 84%
“…65 An observational study of 189 women treated with LMW iron dextran in second and third trimester reported no severe adverse events and only 2% transient infusion reactions. 66 These results corroborated outcomes in other studies showing safety of LMW iron dextran, 67,68 which allows complete replacement of IV iron in a single infusion over 15 to 60 minutes. Despite well-established safety, LMW iron dextran still requires a test dose.…”
Section: Hepcidinsupporting
confidence: 84%
“…Anemia resolved in 95% of subjects, and no SAEs occurred. The authors concluded a large, single, rapidly administered dose of intravenous iron was effective, safe, and convenient [36]. …”
Section: Resultsmentioning
confidence: 99%
“…Intravenous iron therapy is safe in pregnancy and has been demonstrated to correct anemia in more women than oral iron . In addition, efficacy with a single dose intravenous therapy is possible . There are some centers where, resources permitting, erythropoietin therapy is combined with concomitant intravenous iron treatment.…”
Section: Preparation For the Operative Management Of Invasive Placentmentioning
confidence: 99%